2023
DOI: 10.1200/go.22.00348
|View full text |Cite
|
Sign up to set email alerts
|

National Cancer Grid Virtual Tumor Boards of Head and Neck Cancers: An Innovative Approach to Multidisciplinary Care

Abstract: PURPOSE Virtual tumor board (VTB) via videoconference facility involving multiple specialists in the decision making for various tumors is well accepted, especially in high-income countries. Information on virtual tumor boards for head and neck cancers especially from low- and middle-income countries is sparse. In this study, we have audited the findings of the National Cancer Grid VTBs performed for head and neck cancers. METHODS All patients discussed in the head and neck VTBs at our center between December … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…The National Cancer Grid in India has demonstrated the power of this approach to improving access to multidisciplinary decision making particularly for uncommon cancers at a national level, and the value of virtual tumor boards as an educational tool for both trainees and practicing surgeons and physicians. 36 The use of virtual tumor boards has accelerated globally during the COVID-19 pandemic and is now also more common in HICs. Telepathology and teleradiology are two other technology-based approaches that can strengthen cancer care delivery and provide a mechanism for training locally where expertise in an area is lacking.…”
Section: Impact Of Inequitymentioning
confidence: 99%
See 1 more Smart Citation
“…The National Cancer Grid in India has demonstrated the power of this approach to improving access to multidisciplinary decision making particularly for uncommon cancers at a national level, and the value of virtual tumor boards as an educational tool for both trainees and practicing surgeons and physicians. 36 The use of virtual tumor boards has accelerated globally during the COVID-19 pandemic and is now also more common in HICs. Telepathology and teleradiology are two other technology-based approaches that can strengthen cancer care delivery and provide a mechanism for training locally where expertise in an area is lacking.…”
Section: Impact Of Inequitymentioning
confidence: 99%
“…Virtual tumor boards, conducted at a local, regional or international level to support surgeons working outside of major cancer centers allow for access to multidisciplinary expertise that may not be available locally, and shared decision making on recommended treatment and treatment sequencing. The National Cancer Grid in India has demonstrated the power of this approach to improving access to multidisciplinary decision making particularly for uncommon cancers at a national level, and the value of virtual tumor boards as an educational tool for both trainees and practicing surgeons and physicians 36 . The use of virtual tumor boards has accelerated globally during the COVID‐19 pandemic and is now also more common in HICs.…”
Section: How Can We Find Solutions To Tackle These Challenges?mentioning
confidence: 99%
“…We discovered a total of 36 papers using our search criteria. The number of studies at each stage of the screening process is shown in Fig 1 . Study designs of included studies were mostly observational cross-sectional studies (n = 15) [7,[17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Other study designs were retrospective review of records with a cross-sectional survey (n = 12) [5,[31][32][33][34][35][36][37][38][39][40][41], meeting observations with cross-sectional survey (n = 1) [42], mixedmethod design (n = 3) [43][44][45], embedded study design (n = 1) [46], randomized controlled trials (n = 2) [47,48], descriptive qualitative synthesis using free-text cross-sectional surveys (n = 1) [49], and an anthropological analysis (n = 1) [50].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Decision-making. Two studies reported that consensus was frequently reached in VMDTMs [20,35], and, according to one study, there is no difference between IMDTMs and VMDTMs in reaching a consensus [46]. However, one study reported that the level of consensus was slightly lower for VMDTMs compared to in-person meetings [48].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation